Penurunan Etika Sebagai Dampak Kejahatan Siber Terhadap Generasi Muda di Indonesia - Lukman salim nur hakim; Syafiq ijlal islam; Muhamad giosefi; Lilik prihatini (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research explores the impact of cyber crime on the decline in ethics of the younger generation in Indonesia. The main objective is to analyze how cyber attacks affect ethical values among teenagers and students. The research method involves qualitative data analysis to understand the perceptions and experiences of the younger generation towards cyber threats. Data collected includes responses to cyberbullying, online fraud and digital exploitation. Results show that cybercrime undermines moral integrity and triggers ethical decline in online and offline behavior. In responding to this problem, there needs to be a collaborative effort between the government, educators and society to increase digital awareness and education to protect the ethical integrity of the younger generation. The conclusion of this research emphasizes the need for holistic preventive and educational measures to overcome the negative impact of cybercrime on adolescent ethics in Indonesia.